Cone Beam Computed Tomographic Assessment of Bifid Mandibular Condyle - Leila Khojastepour; Shirin Kolahi; Nazi Panahi; Abdolaziz Haghnegahdar (Tehran University of Medical Sciences, 2016)
Objectives: Differential diagnosis of bifid mandibular condyle (BMC) is important, since it may play a role in temporomandibular joint (TMJ) dysfunctions and joint symptoms. In addition, radiographic appearance of BMC may mimic tumors and/or fractures. The aim of this study was to evaluate the prevalence and orientation of BMC based on cone beam computed tomography (CBCT) scans.   Materials and Methods: This cross-sectional study was performed on CBCT scans of paranasal sinuses of 425 patients. In a designated NNT station, all CBCT scans were evaluated in the axial, coronal and sagittal planes to find the frequency of BMC. The condylar head horizontal angulations were also determined in the transverse plane. T-test was used to compare the frequency of BMC between the left and right sides and between males and females. Results: Totally, 309 patients with acceptable visibility of condyles on CBCT scans were entered in the study consisting of 170 (55%) females and 139 (45%) males with a mean age of 39.43±9.7 years. The BMC was detected in 14 cases (4.53%). Differences between males and females, sides and horizontal angulations of condyle of normal and BMC cases were not significant. Conclusion: The prevalence of BMC in the studied population was 4.53%. No significant difference was observed between males and females, sides or horizontal angulations of the involved and uninvolved condyles.